Hello there!
In order to graph the solution, we need to solve it first.
So let's start....
3/7(35x - 14) ≤ 21x/2 + 3
15x -6 ≤ 21x/2 + 3
15x - 21x/2 ≤ 3 + 6
9x/2 ≤ 9
x ≤ 9* 2/9
x ≤ 18/9
x ≤ 2
See the picture for the graph
Please let me know if you have questions about the answer.
Thanks!
Answer:
g(3) = 7
Step-by-step explanation:
g(3) means to substitute "x" for 3.
Change any "x" in the function to 3. Then solve.
Take the function
g(x) = 2x + 1
Substitute x = 3
g(3) = 2(3) + 1
Solve with BEDMAS order (brackets, exponents, division, multiplication, addition, subtraction).
g(3) = 2(3) + 1 Multiply first
g(3) = 6 + 1 Add
g(3) = 7 Answer
<em>Answer</em><em>:</em>
<em>2</em><em> </em><em>out</em><em>. </em><em>of</em><em> </em><em>7</em>
<em>Explanation</em><em>:</em>
<em>First</em><em> </em><em>of</em><em> </em><em>all</em><em> </em><em>There</em><em> </em><em>are</em><em> </em><em>2</em><em> </em><em>C</em><em> </em><em> </em><em>in</em><em> </em><em>the</em><em> </em><em>word</em><em> </em><em> </em><em>and</em><em> </em><em>so</em><em> </em><em>it's</em><em> </em><em>going </em><em>to </em><em>be</em><em> </em><em>2</em><em> </em><em>out</em><em> </em><em>of </em><em>the</em><em> </em><em>total</em><em> </em><em>number</em><em> </em><em>of</em><em> </em><em>words </em><em>in</em><em> </em><em>the</em><em> </em><em>given </em><em>word</em>
<em>2</em><em> </em><em>/</em><em> </em><em>7</em><em> </em>
<em>So </em><em>that</em><em> </em><em>is</em><em> </em><em>the</em><em> </em><em>probab</em><em>ility</em><em> </em>
Answer:
Thursday
Step-by-step explanation:
Positive sign denotes that it has gained
Answer:
Step-by-step explanation:
The given expression to us is ,
Now take the LCM as ( x - 1 ) and Simplify , we have ,
Simplifying further , we get ,
<u>Hence the second option is correct.</u>